Aβ1-42-containing platelet-derived extracellular vesicle is associated with cognitive decline in Parkinson’s disease - Wang, Ziyu; Zheng, Yuanchu; Cai, Huihui; Yang, Chen; Li, Siming; Lv, Hong; Feng, Tao; Yu, Zhenwei (Frontiers in Aging Neuroscience, 2023)
Background: Cortical amyloid deposition is a common observation in Parkinson's disease dementia (PDD) patients. Aβ1-42 is linked to a more rapid progression of dementia. Platelets, which degranulate upon activation, are a primary source of Aβ. It has been repeatedly reported that peripheral extracellular vesicles (EVs) can partially reach the central nervous system. Thus, we speculate that activated platelet-derived Aβ1-42-containing EVs (PEV-Aβ1-42) play a crucial role in the cognitive decline of PD patients. Methods: The study included 189 participants: 66 with non-dementia PD, 73 with PDD, and 50 healthy controls. All participants underwent blood collection and clinical assessments. 20 PD patients underwent re-examination and repeated blood collection 14 months later. A nano-scale flow cytometry assay was used to detect PEVs and PEV-Aβ1-42 using fluorescence-labeled CD62P and Aβ1-42 antibodies. Results: PDD patients had higher PEV-Aβ1-42 concentrations than healthy controls (p = 0.028). The ratio of PEV-Aβ1-42 to PEV was significantly higher in PDD patients compared to those in non-dementia PD and healthy controls (pPD-ND < 0.001, pHC = 0.041). The PEV-Aβ1-42/PEV ratio appears to influence the odds of developing dementia (OR = 1.76, p < 0.001). The change in the PEV-Aβ1-42/PEV ratio was also correlated with cognitive decline over 14 months (r = -0.447, p < 0.05). Conclusions: The plasma PEV-Aβ1-42/PEV ratio may serve as a diagnostic and prognostic biomarker for PDD patients.